Penerapan Model Kooperatif Tipe Jigsaw berbantuan Media Word Wall untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VB pada Materi Norma dalam Kehidupanku di UPTD SD Negeri Sikumana 1 - Marchel H. Djami Riwu; Martha Khristina Kota; Rulnayu Oan (ARZUSIN, 2025)
Low student interest and motivation in the topic Norms in My Life have led to minimal engagement and suboptimal learning outcomes. This study aims to improve student learning achievement through the implementation of the cooperative learning model of the jigsaw type, supported by word wall media. The research employed a Classroom Action Research (CAR) approach consisting of four main stages: planning, implementation, observation, and reflection. Data collection was systematically conducted through observation, pretest and posttest evaluations, and relevant documentation. A test instrument was used to measure the difference in learning outcomes before and after applying the jigsaw model. The study involved 18 fifth-grade students from UPTD SD Negeri Sikumana 1. The results showed a significant improvement in learning achievement: in the pre-cycle, only 4 students met the minimum competency criteria (60.1%); in Cycle I, this increased to 9 students (70%); and in Cycle II, 15 students (91.1%) achieved the target. These findings demonstrate that the jigsaw cooperative learning model, supported by word wall media, is effective in enhancing student learning outcomes. The implications of this study span theoretical aspects in the development of collaborative learning design, as well as practical benefits for students, teachers, schools, and researchers in creating more meaningful and contextualized learning experiences.